2002
DOI: 10.1002/1522-2675(200202)85:2<559::aid-hlca559>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Screening of 2-Substituted 5,6-Dihydro-5-oxo- 4H-1,3,4-oxadiazine-4-propanenitriles and of Their Intermediates

Abstract: To evaluate the effect of substituents on biological activities of electron-rich N-containing heterocycles, the variably 2-substituted 5,6-dihydro-5-oxo-4H-1,3,4-oxadiazine-4-propanenitriles 26 ± 33 were synthesized and evaluated for antibacterial, antifungal, and enzyme-inhibition activities. The target compounds were obtained from alkyl 4-or 3-hydroxy benzoates 1 and 2, respectively, and from methyl indoleacetate 3. The phenolic OH group of benzoates 1 and 2 were substituted with p-toluenesulfonyl ( 3 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…According to US Environmental Protection Agency 20 and International Agency for Research on Cancer 21 , dioxane is classified as a carcinogenic compound and it is a potential carcinogen to human. The result obtained for product prepared in ethanol is in agreement with the work by Khan et al 2002 which showed that alkylation of hydrazides at the N 1 or N 2 atom strongly dependent on the nature of the solvent 22 . In neutral medium, terminal N 2 atom is alkylated whereas, in the presence of a strong base such as sodium or sodium methoxide, alkylation at the internal N 1 atom is favored in aprotic solvents such as ether and benzene, while protic solvents such as ethanol will lead to N 2 substitution.…”
Section: Effect Of Solventsupporting
confidence: 88%
“…According to US Environmental Protection Agency 20 and International Agency for Research on Cancer 21 , dioxane is classified as a carcinogenic compound and it is a potential carcinogen to human. The result obtained for product prepared in ethanol is in agreement with the work by Khan et al 2002 which showed that alkylation of hydrazides at the N 1 or N 2 atom strongly dependent on the nature of the solvent 22 . In neutral medium, terminal N 2 atom is alkylated whereas, in the presence of a strong base such as sodium or sodium methoxide, alkylation at the internal N 1 atom is favored in aprotic solvents such as ether and benzene, while protic solvents such as ethanol will lead to N 2 substitution.…”
Section: Effect Of Solventsupporting
confidence: 88%
“…Hydrazides are organic compounds primarily known for their medical applications in the treatment of tuberculosis [1,2] as well as antibacterial agents and fungicides [3,4]. Hydrazides are good ligands for binding metal ions and their coordination chemistry has grown since it was discovered that metal complexes have stronger antimicrobial action than pure ligand and metal salt [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazides are good ligands for binding metal ions and their coordination chemistry has grown since it was discovered that metal complexes have stronger antimicrobial action than pure ligand and metal salt [3][4][5]. The last possibility stimulates our efforts in the preparation of new metal complexes with 4-hydroxybenzhydrazide (4hbah), to be further tested for biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that 4-HBAH is able to induce resistance to tomato wilt disease [9]. The presented compound has also been used in syntheses of more complicated enzyme inhibitors [10].…”
Section: Introductionmentioning
confidence: 96%